Role of Endobronchial Ultrasound-guided Transbronchial Needle Aspiration in the Diagnosis and Management of Mediastinal Cyst. Issue 2 (April 2020) - Aravena, Carlos; Patel, Jinesh; Goyal, Abha; Jaber, Wissam; Khemasuwan, Danai; Machuzak, Michael; Cicenia, Joseph; Gildea, Thomas; Sethi, Sonali; Mehta, Atul C.; Almeida, Francisco A.
Abstract : Background: Foregut cysts account for >50% of cystic lesions in the mediastinum, of which bronchogenic cysts are most common. Surgical resection is the most definitive approach for its diagnosis and treatment. A recent systematic review, however, suggests that endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) has a role in the management of bronchogenic cyst. We report our experience with EBUS-TBNA in the diagnosis and management of bronchogenic cysts. Methods: Medical records of patients with evidence of mediastinal cysts who underwent EBUS-TBNA between 2008 and 2016 were reviewed. The primary aims of this study were to assess EBUS-TBNA diagnostic yield of peri-bronchial cysts and their specific type/origin and to determine its short-term and long-term drainage efficacy. Results: A total of 26 patients met the inclusion criteria. The cytopathology diagnosis was compatible with bronchogenic cyst in 4 cases, pleural-pericardial cyst in 3 cases, and 19 were indeterminate cysts. Successful long-term treatment occurred in 5.5% of the subjects. One patient developed inflammatory pericarditis after EBUS-TBNA. Conclusion: Diagnostic and therapeutic yield of EBUS-TBNA for mediastinal cysts is limited and surgical resection remains the treatment of choice.